Os novos desafios à teoria jurídica com origem na reconfiguração e no redimensionamento do direito internacional - Correia, José Evandro Alencar (2015)
The social reality passed through many changes, especially after the structural changes in the second half of twenty century, and beginning of twenty first century. With Law could not be different. In the national environment, the constitution idea has been changed and incorporated a diversity of new rights, this producing friction between the powers and new difficulties to get coherence inside the own State organization, which have a big diversification of norms and values. In the external environment, the Law also has been through many changes. The role of States is reshaped, and an extensive structure of international organizations is built. Beyond this factors, it also noticeable the rise of private actors as NGOs and multinational companies. This two new actors act at the global scenario in increasingly intense way, creating codes of conduct for their behavior and influence a big diversity of fields. The new possibilities of interaction in the global framework made that International Law pass through and thematic expansion, in the number of rules and in the international courts. Before this new factual scenario some changeless emerge. Are the relationship among themes and norms consistent? The many rules that act in thematic fields (economic, human rights, environmental, technology, financial, health, building standards) and this make that the relationship act in thematic fields and not along territorial lines. Towards this fact, the classic mechanisms of resolution of antinomies seems to be of little help. The International Law is seen as a fragmented structure and incoherent. The theoretical challenge is to reconcile and systematize this reality. Rethink the coherence and fragmentation, in a pluralistic context, may be a way of revitalization of the legal theory in the search of others explanatory models and in the development of a new methodological attitude.